International consensus guidelines on the role of diagnostic endoscopic ultrasound in the management of chronic pancreatitis: recommendations from the working group for the international consensus guidelines for chronic pancreatitis in collaboration with the International Association of Pancreatology, the American Pancreatic Association, the Japan Pancreas Society, and European Pancreatic Club - Wilcox, C. Mel; Gress, Thomas; Boermeester, Marja; Masamune, Atsushi; Lévy, Philippe; Itoi, Takao; Varadarajulu, Shyam; Irisawa, Atsushi; Levy, Michael; Kitano, Masayuki; Garg, Pramod; Isaji, Shuiji; et al. (Pancreatology, 2020)
Background - Chronic pancreatitis (CP) is a complex inflammatory disease with variable presentations and outcomes. This statement is part of the international consensus guidelines on CP, specifically on the diagnostic role of endoscopic ultrasound (EUS). - Methods - An international working group with experts on the role of diagnostic EUS in the management of CP from the major pancreas societies (IAP, APA, JPS, and EPC) evaluated two key statements generated from evidence on two questions deemed to be the most clinically relevant. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach was used to evaluate the level of evidence available for each statement. To determine the level of agreement, the working group voted on each statement for strength of agreement, using a nine-point Likert scale in order to calculate Cronbach’s alpha reliability coefficient. - Results - Strong consensus was obtained for both of the following statements [1]. The ideal threshold number of EUS criteria necessary to diagnose CP has not been firmly established, but the presence of 5 or more and 2 or less strongly suggests or refutes the diagnosis, respectively. The Rosemont scoring system standardizes the reporting of EUS signs indicative of chronic pancreatitis, but further studies are needed to demonstrate an overall improvement of its diagnostic accuracy over conventional scoring [2]. Specificity, inter- and intra-observer variability and pre-test probability limit the reliability and utility of EUS to help diagnose CP especially early stages of the disease. - Conclusions - The presence of 5 or more and 2 or less EUS criteria strongly suggests or refutes the diagnosis of CP, respectively. Intra-observer variability still limits the role of EUS in diagnosing CP especially early stage disease.
Gesehen am 23.09.2020